A nova cultura científica na obstetrícia e sues efeitos profissionais (séc. XIX) - Carneiro, Marinha do Nascimento (História: revista da Faculdade de Letras da Universidade do Porto, 2018)
The role of the midwife was to care mothers in childbirth. For centuries, in the agrarian society, her action was based in a folk knowledge. Since the 19th century, her graduation was taken in academic institutions, due to the new institutional conditions, leaded by the medical profession and its scientific strategies: the midwives should be supervised by medicine, according the knowledge and technology developed in the medical obstetric.